Através da TAG e o que Alice encontrou por lá : memória, comunicação e consumo em um clube de livros - Bacega, Débora Regina (2019)
This research study is focused on the recently-created book clubs as memory of culture and culture of communicational and consumption phenomena. A flourishing event since 2014, the rising of 15 clubs of book subscriptions illustrates the relevance of this study. The communication and consumption practices triggered by these clubs in a curatorship is the theoretical object of this study. Its empirical object is based on the TAG, that has set up a curatorship structured in the consumption of memories, affections and literary experiences in a book club. The issue here is to understand how the club articulates the curatorship. The general purpose is to identify the communication and consumption practices trigger in a curatorship, its interfaces with memory culture and affections. The specific objectives are to map and identify the main characteristics of two previous experiences in a book clubs (Clube do Livro and Círculo do Livro); to map and analyze the objects to operates the symbolic consumption of the memories and affections as a ritual and to identify and investigate the objects which operates the symbolic consumption of the calendar rites and recollections. The semiotic theory of culture proposed by Iúri Lotman and Boris Uspênski of the Tartu-Moscow School is adopted. It presents the cultural analysis of consumption as postulated by Mary Douglas and Baron Isherwood. There are reflections over the new spirit of capitalism of Luc Boltanski and Ève Chiapello. The studies of such authors as Pierre Nora, Paul Ricoeur, Baruch Espinosa, Hans Obrist, Hans Gumbrecht, Roger Chartier, Michèle Petit, Mônica Nunes and Harry Pross are presented. Qualitative research is based on bibliographical and documentary research, as well as empirical observations with the case study method. The corpus consists of objects which operates memories, affections and reminders; and documents posted on the club's website and media. It seeks to understand how the curatorship of memory can preserve culture memories, affective and media. This aims to demonstrate how the curatorship of TAG articulates symbolic consumption in the rituals of a contemporary book club.